Post-harmonised European National Travel Surveys - Christensen, Linda; Vázquez, Natalia Sobrino (Proceedings from the Annual Transport Conference at Aalborg University, 2013)
Look-up tables are collected and analysed for 12 European National Travel Surveys (NTS) in a harmonized way covering the age group 13-84 year. Travel behaviour measured as kilometres, time use and trips per traveller is compared. Trips per traveller are very similar over the countries whereas kilometres differ most, from minus 28% for Spain to plus 19% and 14% for Sweden and Finland. It is shown that two main factors for differences are GDP per capita and density in the urban areas. The latter is the main reason for the low level in Spain. Mode share is except for Spain with a very high level of walking trips rather similar with a higher level of cycling in the Netherlands, more public transport in Switzerland, and more air traffic in Sweden. Normally kilometres per respondent / inhabitant is used for national planning purpose and this is very affected by the share of mobile travellers. The immobile share is varying between 8 and 28% with 6 NTS at a 15-17% level. These differences are analysed and discussed and it is concluded that the immobile share should be a little less than 15-17% because it is assessed that some short trips might have been forgotten in these 6 countries. The share has a downward tendency with higher density. The resulting immobile share is very dependent on data collection methodology, sampling method, quality of interviewer felt-work etc. The paper shows other possibilities to improve local surveys based on comparison with other countries.